A nanoscale redox-active composite as a low-fouling interface for capacitive assaying - Fernandes, Flávio C. Bedatty [UNESP]; Andrade, Juliana R. [UNESP]; Bueno, Paulo R. [UNESP] (Elsevier, 2019)
An electro-active nanoscale composite was engineered to serve as an alternative to monolayers in a capacitive biosensing platform. An electrochemical impedance-derived spectroscopic method was applied to analyse the response of this nanoscale (c.a. 9 nm thickness) composite to detect C-reactive protein. The composite was successfully assembled over a conductive electrode and built up by conjugating graphene oxide sheets into a self-assembled 11-ferrocenyl-undecanethiol structure, forming a molecular composite concomitantly coated with zwitterionic methacrylate-based monomers that served as the non-fouling component of the composite. Finally, the functionalization of a composite with receptors allowed the successful testing of its electro-analytical ability to detect C-reactive protein in both phosphate-buffered saline and neat human serum samples.
Keywords: Electrochemical impedance spectroscopy; Immittance function electro-analysis; Low-fouling; Nanoscale composite; Zwitterionic compound